Trilogía postcolonial: Journey On, Aba Wama y Gariganus’ Exile - Zárate Fernández, Marcela Patricia (Diálogos Latinoamericanos, 2018)
The literature of Latin America informs and captivates lectors through a myriad of sociocultural, political and economic contexts, thus validating it as an artistic expression representative of those postcolonial communities that authors wish to engage. In the case of postcolonial literature, both contemporary and historical events play a significant role in the development of a nation’s distinct identity and facilitate an incipient society’s recognition as an independent region. In this article, I illustrate how the three-part series of books Journey On, Aba Wama, and Gariganus’ Exile by Belizean author Nelita Doherty contribute significantly to the creation of postcolonial Belize through the establishment, struggles, and survival of the Afro-indigenous Garifuna community. This work critically analyzes themes such as emancipation, the concept of “nation”, a feminist perspective of protecting the nation, cultural heritage and remembrance, and subalternity viewed through the lenses of macrohistories and microhistories.